PERLINDUNGAN KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJA STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) DI KOTA PEKANBARU - ANGGA KURNIAWAN A.P; Rika Lestari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Health and safety ( hereinafter referred to as K3 ) is a program created for the workers / laborers and employers as prevention ( preventive ) for the incidence of occupational accidents and diseases caused by working relationships within the work environment by identifying things that could potentially cause accidents and disease due to the employment relationship , and anticipatory action if this happensProtection work can be done either by providing compensation , guidance , and by increasing recognition of rights - human rights , socio-economic and physical protection through norms within the company.The purpose of this study was to determine how to shape the protection of health and safety at worker / operator Fuel Filling Station General ( gas stations) in Sub Tangkerang Central Pekanbaru and to know the efforts to overcome obstacles to the implementation of the protection of health and safety at pekrja / operators General Fuel Filling station in the Village of Central Tangkerang Pekanbaru .By using sociological research methods , namely the law of sociological research , legal conceptualized as a social institution in real terms associated with social variables other.Results of this study are safety and health protection of workers / operators General Fuel Filling Station District of Sail and Village Middle Tangkerang Pekanbaru is still not optimal. It is based on the rule prohibiting companies to use personal protective equipment such as respiratory protective equipment . To implement health and safety , the company regularly registered to the Health Insurance Service Agency ( BPJS ) Employment.Key words: Law enforcement - pickups